Association Between E-FABP Levels, Disease Severity, and Metabolic Parameters in Hidradenitis Suppurativa - Seyirci, Mehmet Ali; Korkmaz, Selma; Ayvaz Çelik, Havva Hilal; Şirin, Fevziye Burcu; Bedir, Mehmet; Orhan, Hikmet (Dermatology Practical & Conceptual, 2026)
Introduction: Studies have shown that hidradenitis suppurativa (HS) is associated with obesity, dyslipidemia, hypertension, metabolic syndrome, and some autoinflammatory diseases. Studies on E-FABP, a member of the fatty acid binding protein family, suggest that this protein may be associated with psoriasis, obesity, metabolic syndrome, atherosclerosis, and autoimmune diseases.Objectives: The aim of this study was to compare serum E-FABP levels in patients with HS and in healthy control subjects and to investigate the relationship between disease severity and metabolic parameters and serum E-FABP levels.Methods: Forty-four HS patients and 45 healthy subjects were included in the study. In the patient and control groups, hs-CRP, routine biochemistry parameters, and serum lipid profiles were measured. Serum E-FABP levels were also determined by ELISA method. Blood pressure, pulse rate, and body measurements were also recorded in the patient and control groups. Obtained data were analyzed with SPSS 22.0.Results: Serum E-FABP levels were found to be statistically significantly higher in the HS group than in healthy controls. However, no significant correlation was found between serum E-FABP levels and disease severity scores. The effect of E-FABP on the development of HS was determined by multivariate logistic regression analysis independent of age, sex, BMI, and hs-CRP. It was determined that the increase in E-FABP level increased the risk of HS development independently of other risk factors.Conclusions: According to this study, E-FABP may be associated with the pathogenesis of HS rather than with disease severity or metabolic conditions.